1999
DOI: 10.1143/jjap.38.4136
|View full text |Cite
|
Sign up to set email alerts
|

Crystallite Size Dependence of Plasmon Energies in Polycrystalline Graphite Observed by Reflected Electron Energy Loss Spectroscopy

Abstract: A comprehensive analysis of gened relativistic spacetimes which admit a shearfree, irrotational and geodesic time-like coogruence is presented. The equations governing the models for a gened energy-momentum tensor are wrilten down. Coordinates in which the metric of such spacetimes takes on a simplified form are established. The general subwses of 'zero anisotropic stress', 'zero heat-flux vector' and 'two-component Ruids' are investigated. In particular, perfect-fluid Friedmann-Robertson-Walker models and spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 5 publications
2
21
0
Order By: Relevance
“…The intensity was found to reduce by an average of 40% relative to the bulk, which indicates a reduction in the degree of π bonding. These results are in line with those from polycrystalline graphite in [36] where a correlation between π plasmon energy and relative intensity was also found; and with results from a graphitization series in [18] where EELS spectra from pre-graphitized material show a π plasmon intensity of ca. 50% of that in the graphitized product.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The intensity was found to reduce by an average of 40% relative to the bulk, which indicates a reduction in the degree of π bonding. These results are in line with those from polycrystalline graphite in [36] where a correlation between π plasmon energy and relative intensity was also found; and with results from a graphitization series in [18] where EELS spectra from pre-graphitized material show a π plasmon intensity of ca. 50% of that in the graphitized product.…”
Section: Resultssupporting
confidence: 90%
“…In all cases, the reduction in π plasmon energy was to ca. 5 ± 0.5eV suggesting a reduction in crystallinity and density possibly due to sub 10nm crystallite sizes [36]. The normalised intensity of the π plasmon peak was also measured; a π plasmon window from 4.5eV to 8eV and total intensity window from -3eV to 50eV were used.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, it was observed that the work function increased with the dosage of Ar C in a certain range, and the plasmon and the C plasmon energies decreased by increasing the dosage above certain doses. The relationship between the plasmon energy and the relative peak intensity in Ar C -irradiated graphite, and comparison with our previous work, 5 were also discussed.…”
Section: Introductionmentioning
confidence: 65%
“…5 The relationship between the plasmon energies and the relative peak intensities for Ar C -irradiated graphite and polycrystalline graphite is plotted in Fig. 5.…”
Section: Comparison Of the P Plasmon Peaks With Those For Polycrystalmentioning
confidence: 99%
See 1 more Smart Citation